If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(4t + -4) + 7t = 3t + -3 Reorder the terms: -5(-4 + 4t) + 7t = 3t + -3 (-4 * -5 + 4t * -5) + 7t = 3t + -3 (20 + -20t) + 7t = 3t + -3 Combine like terms: -20t + 7t = -13t 20 + -13t = 3t + -3 Reorder the terms: 20 + -13t = -3 + 3t Solving 20 + -13t = -3 + 3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3t' to each side of the equation. 20 + -13t + -3t = -3 + 3t + -3t Combine like terms: -13t + -3t = -16t 20 + -16t = -3 + 3t + -3t Combine like terms: 3t + -3t = 0 20 + -16t = -3 + 0 20 + -16t = -3 Add '-20' to each side of the equation. 20 + -20 + -16t = -3 + -20 Combine like terms: 20 + -20 = 0 0 + -16t = -3 + -20 -16t = -3 + -20 Combine like terms: -3 + -20 = -23 -16t = -23 Divide each side by '-16'. t = 1.4375 Simplifying t = 1.4375
| y=180x+700 | | -2x+3+x=4 | | 8x(x+7)=6(x-4) | | -5/3v+4=-7/4v-4/3 | | -82=-4(4-6p)+6 | | -3(3x-7)+9=-9x+30 | | 14x-10=x+3x-2x | | x*1=(6/8) | | 1x+3x=48 | | -9=-8(k-5)+3(1+7k) | | 5(k-2)=8(7) | | -2=k-14 | | 6.76x+49=45.6976+7x | | 82.53=315% | | 5u^2-13u=6 | | 5x/14+2x/14 | | -5f-18=2 | | f(5)g(5)=0 | | 7/15*21/10 | | 3(a-2)=2(9) | | 3.5x=31.5 | | 9x+3*69= | | 3u^2-5u-2=6 | | 2/3+3x/4=71/12 | | 3.3q-3.2-5.3q=3.0q-5.2 | | 0(-6)= | | -3/2*2 | | x+56=0.24(x+56) | | x/6-7=2/3 | | -7y+8=8y+1 | | 4x+3(5x+4)=183 | | 2f+5g=1-fg |